Brief review: Applications of nanocomposite in electrochemical sensor and drugs delivery - Haq Khan, Zia Ul; Khan, Taj Malook; Khan, Amjad; Shah, Noor Samad; Muhammad, Nawshad; Tahir, Kamran; Iqbal, Jibran; Rahim, Abdur; Khasim, Syed; Ahmad, Iftikhar; Shabbir, Khadija; Gul, Noor Shad; et al. (Frontiers in Chemistry, 2023)
The recent advancement of nanoparticles (NPs) holds significant potential for treating various ailments. NPs are employed as drug carriers for diseases like cancer because of their small size and increased stability. In addition, they have several desirable properties that make them ideal for treating bone cancer, including high stability, specificity, higher sensitivity, and efficacy. Furthermore, they might be taken into account to permit the precise drug release from the matrix. Drug delivery systems for cancer treatment have progressed to include nanocomposites, metallic NPs, dendrimers, and liposomes. Materials' mechanical strength, hardness, electrical and thermal conductivity, and electrochemical sensors are significantly improved using nanoparticles (NPs). New sensing devices, drug delivery systems, electrochemical sensors, and biosensors can all benefit considerably from the NPs' exceptional physical and chemical capabilities. Nanotechnology is discussed in this article from a variety of angles, including its recent applications in the medical sciences for the effective treatment of bone cancers and its potential as a promising option for treating other complex health anomalies via the use of anti-tumour therapy, radiotherapy, the delivery of proteins, antibiotics, and vaccines, and other methods. This also brings to light the role that model simulations can play in diagnosing and treating bone cancer, an area where Nanomedicine has recently been formulated. There has been a recent uptick in using nanotechnology to treat conditions affecting the skeleton. Consequently, it will pave the door for more effective utilization of cutting-edge technology, including electrochemical sensors and biosensors, and improved therapeutic outcomes.